2018
DOI: 10.1080/14756366.2018.1499627
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and its sulphonamide derivative simultaneously potentiateanti-cholinesterase activity of donepezil and inhibit beta-amyloid aggregation

Abstract: The aim of this study was to assess in vitro the effects of sulphenamide and sulphonamide derivatives of metformin on the activity of human acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), establish the type of inhibition, and assess the potential synergism between biguanides and donepezil towards both cholinesterases (ChEs) and the effects on the β-amyloid aggregation. Sulphonamide 5 with para-trifluoromethyl- and ortho-nitro substituents in aromatic ring inhibited AChE in a mixed-type manner at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[16][17][18] Similarly, another study has shown that Met, and its derivatives, can improve the activity of human acetylcholinesterase (AChE) and inhibit beta-amyloid aggregation. 19 However, epidemiological researchers have reported inconsistencies concerning the studies that Met is related to an increased risk of neurodegenerative diseases (NDs). 3,20,21 Some studies suggested a reduced risk of NDs with Met treatment, [22][23][24][25][26][27][28] while others reported no association.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Similarly, another study has shown that Met, and its derivatives, can improve the activity of human acetylcholinesterase (AChE) and inhibit beta-amyloid aggregation. 19 However, epidemiological researchers have reported inconsistencies concerning the studies that Met is related to an increased risk of neurodegenerative diseases (NDs). 3,20,21 Some studies suggested a reduced risk of NDs with Met treatment, [22][23][24][25][26][27][28] while others reported no association.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy may be raised in treating cancers and neurodegenerative diseases. Among the targeted therapeutic agents, AMPK activator drugs, e.g., metformin and berberine, have potential therapeutic applications in metabolic disorders, neurodegenerative diseases, and cancers [84][85][86][87][88][89][90][91]. Our recent works and this report revealed that n-BP can functionally activate AMPK [81], although the details of its mechanism in autophagy remain an effort to be addressed.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study showed that phenformin with an AChE SI value of 0.052 indicating that it was BChE selective did not alter the AChE SI value of donepezil, whereas a metformin sulphonamide derivative with an AChE SI value of 3.23 increased the AChE SI value of donepezil around 200-fold higher. On the other hand, metformin with an AChE SI value of > 425.53 did not alter the AChE SI value of donepezil either (Markowicz-Piasecka et al, 2018). Many factors may thus, be at work for this apparent discrepancy.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 82%